The Phonology of Edo Ideophones - Victor Edosa Omozuwa; E̩dosa James Edionhon (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2026)
This study addresses the inadequately documented phonological behaviour of ideophones in E̩do, an E̩doid language of Southern Nigeria, where these forms are often noted but lack detailed analysis. It aims to provide a systematic account of the segmental and suprasegmental features, as well as the phonological processes, that characterize E̩do ideophones. Data were obtained through oral interviews with competent native speakers, and the analysis is situated within the framework of basic linguistic theory allowing for a direct description of attested forms in natural speech. Structurally, ideophones exhibit a wider syllable range, extending from disyllabic to predominantly polysyllabic forms, thereby contrasting with the typically shorter non-ideophonic lexicon. While E̩do generally restricts consonant clustering, limited cluster-like sequences arise through glide formation in ideophonic forms. Therefore, this study contributes to a clearer understanding of the phonological structure of E̩do ideophones and underscore their structural markedness within the language.